Viral Bcl-2-mediated evasion of autophagy aids chronic infection of gammaherpesvirus 68. - Xiaofei E; Seungmin Hwang; Soohwan Oh; Jong-Soo Lee; Joseph H Jeong; Yousang Gwack; Timothy F Kowalik; Ren Sun; Jae U Jung; Chengyu Liang (PLoS Pathogens, 2009)
Gamma-herpesviruses (gammaHVs) have developed an interaction with their hosts wherein they establish a life-long persistent infection and are associated with the onset of various malignancies. One critical virulence factor involved in the persistency of murine gamma-herpesvirus 68 (gammaHV68) is the viral homolog of the Bcl-2 protein (vBcl-2), which has been implicated to counteract both host apoptotic responses and autophagy pathway. However, the relative significance of the two activities of vBcl-2 in viral persistent infection has yet to be elucidated. Here, by characterizing a series of loss-of-function mutants of vBcl-2, we have distinguished the vBcl-2-mediated antagonism of autophagy from the vBcl-2-mediated inhibition of apoptosis in vitro and in vivo. A mutant gammaHV68 virus lacking the anti-autophagic activity of vBcl-2 demonstrates an impaired ability to maintain chronic infections in mice, whereas a mutant virus lacking the anti-apoptotic activity of vBcl-2 establishes chronic infections as efficiently as the wild-type virus but displays a compromised ability for ex vivo reactivation. Thus, the vBcl-2-mediated antagonism of host autophagy constitutes a novel mechanism by which gammaHVs confer persistent infections, further underscoring the importance of autophagy as a critical host determinant in the in vivo latency of gamma-herpesviruses.